Machine learning in geo-risk susceptibility mapping - Moayedi, Hossein; Ahmadi Dehrashid, Atefeh; Gör, Mesut (Elsevier, 2025)
[Abstract Not Available]
Keywords: Learning systems; Machine learning; Machine-learning; Susceptibility mapping; Mapping